Pharmacokinetic Evaluation of the CYP3A4 and CYP2D6 Drug‐Drug Interaction and CYP3A4 Induction Potential of Omecamtiv Mecarbil: Two Open‐Label Studies in Healthy Subjects. Issue 2 (19th June 2021) - Trivedi, Ashit; Malik, Fady I.; Jafarinasabian, Pegah; Zhang, Hanze; Flach, Stephen; Abbasi, Siddique; Dutta, Sandeep; Lee, Edward
Abstract: Omecamtiv mecarbil (OM) is a cardiac myosin activator under development for the treatment of heart failure. The effect of CYP3A4 and CYP2D6 inhibition on OM pharmacokinetics and the potential for OM to induce CYP3A4 was assessed in 2 studies. Study 1, part A, assessed the effect of ketoconazole 200 mg on the pharmacokinetics of OM 10 mg in CYP2D6 extensive metabolizers (EMs; n = 8) or poor metabolizers (PMs; n = 8). Study 1, part B, assessed the effect of diltiazem 240 mg on the pharmacokinetics of OM 10 mg (EM; n = 8). Study 2 assessed the effect of OM 25 mg on the pharmacokinetics of midazolam 5 mg (n = 14). Coadministration with ketoconazole led to 51% and 31% increases in OM AUCinf in EM and PM subjects, respectively, whereas OM Cmax remained similar (3% higher and 14% lower for EM and PM subjects, respectively). No changes in OM pharmacokinetics were observed in EM subjects following coadministration with diltiazem. Midazolam AUCinf and Cmax decreased by 18% and 10%, respectively, when coadministered with OM. In conclusion, CYP3A4 and CYP2D6 inhibitors are unlikely to have a clinically significant effect on the pharmacokinetics of OM. In addition, OM is unlikely to have a clinically relevant effect on the pharmacokinetics of CYP3A4 substrates.